REKONSTRUKSI PENDIDIKAN ISLAM (Menimbang Pemikiran Muhammad Abduh) - -, Siswanto (State Islamic Institute of Madura, 2009)
As modernist theologian, Abduh states that science and Islam are not contradiction; religion and scientific thought collaborate in diffrerent level. It provides new ideas in two crucial points; first of all, it generally emphasis on the role of logic in Islam. Secondly, it restates the basic ideas of Islam as opening for growing new ideas and seeking modern knowledge. Therefore, reconstruction is focused on to establish education system producing educated persons who possess both vigorous religion beliefs or become modern islamic scholars and functional education including universal education for all people, either male or female.